Formative assessment in higher education: an exploratory study within programs for professionals in education - Parmigiani, Davide; Nicchia, Elisabetta; Murgia, Emiliana; Ingersoll, Marcea (Frontiers in Education, 2024)
This study explores how prospective professionals in higher education can learn about and apply formative assessment methods relevant to their future educational workplaces. In the academic year 2022-23, 156 pre-service teachers, social workers, and heads of social services took part in a three-stage mixed-method study on university learning experiences involving formative assessment practices. They were exposed to self-, peer-, and group-assessment strategies. Data collected after each stage revealed participants' perspectives on each method. Findings show that students who engaged in formative assessment comprehended assessment complexity and were motivated to use diverse assessment forms. Formative assessment proves effective for both evaluation and development, supporting higher education students in honing assessment competencies for future professional roles in educational and social sectors.